The Short Run and Long Run Causality between Financial Development and Economic Growth in the Middle East - Karim Eslamloueyan; Emad Aldeen Sakhaei (فصلنامه پژوهش‌های اقتصادی ایران, 2011)
Using panel data error correction models, we investigate the short- and long-run causality between financial development and economic growth in the Middle East. Three different indicators are used to measure financial developments. Generalized Least Square (GLS) method with cross-section Seemingly Unrelated Regression (SUR) and fixed effects in cross dimension is used to estimate the models. Our estimation results suggest that there is bidirectional causality between financial development and economic growth in both the short- and long run. The result underscores the feedback between finance and growth and hence advocates the third view that emphasizes on mutual causality between financial development and economic growth. In other words, finance can promote growth and in turn output growth will enhance financial development in the Middle East. This result can have important policy implications for both policymakers and international institutions.